2015
DOI: 10.4238/2015.july.17.16
|View full text |Cite
|
Sign up to set email alerts
|

Stripe rust resistance and dough quality of new wheat - Dasypyrum villosum translocation lines

Abstract: ABSTRACT. The transfer of agronomically useful genes from wild wheat species into cultivated wheat is one of the most effective approaches to improvement of wheat varieties. To evaluate the transfer of genes from Dasypyrum villosum into Triticum aestivum, wheat quality and disease resistance was evaluated in two new translocation lines, T1DL•1V#3S and T1DS•1V#3L. We examined the levels of stripe rust resistance and dough quality in the two lines, and identified and located the stripe rust resistant genes and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Genes at locus Glu-V1 for HMW storage protein subunits are located on chromosome 1V, and prolamin genes are located on chromosomes 1V and 4V ( Montebove et al, 1987 ; De Pace et al, 2001 ; Vaccino et al, 2010 ). The recently identified two wheat— D. villosum homozygous translocations confirmed that the HMW-GS gene of D. villosum was located on both 1VL and 1VS ( Dong et al, 2013 ; Zhang et al, 2014 ; Zhao et al, 2015 ). In the present study, we also cloned ten sequences from Dasypyrum sequences and identified the different lengths of HMW-GS sequences in both D. breviaristatum and the wheat— D. breviaristatum partial amphiploid TDH-2.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Genes at locus Glu-V1 for HMW storage protein subunits are located on chromosome 1V, and prolamin genes are located on chromosomes 1V and 4V ( Montebove et al, 1987 ; De Pace et al, 2001 ; Vaccino et al, 2010 ). The recently identified two wheat— D. villosum homozygous translocations confirmed that the HMW-GS gene of D. villosum was located on both 1VL and 1VS ( Dong et al, 2013 ; Zhang et al, 2014 ; Zhao et al, 2015 ). In the present study, we also cloned ten sequences from Dasypyrum sequences and identified the different lengths of HMW-GS sequences in both D. breviaristatum and the wheat— D. breviaristatum partial amphiploid TDH-2.…”
Section: Discussionmentioning
confidence: 74%
“…Dasypyrum species possess agronomically important genes controlling traits including disease resistance, high protein contents and drought adaptation, which represent valuable resources for wheat improvement over the world ( Zhang et al, 2005 ; De Pace et al, 2011 ). The annual species Dasypyrum villosum carries effective resistance genes to several fungal pathogens of wheat and has genes which may have a positive contribution to quality improvement when transferred into a wheat background ( Chen et al, 1995 ; Patrizia et al, 2010 ; Qi et al, 2011 ; Zhao et al, 2010 , 2015 ). It is thus essential to localize the novel seed proteins from D. villosum and to characterize the HMW-GS genes from wheat— D. villosum derivatives ( Zhong and Qualset, 1993 ; Vaccino et al, 2010 ; Zhang et al, 2014 ; Yang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, Yildirim et al [ 17 ] tested the stripe rust reactions of D. villosum accessions, and the results showed that, of the 115 D. villosum accessions tested, 41 (35.65%) were resistant to stripe rust, indicating that D. villosum provides a vast pool of genes for stripe rust resistance. However, there only a few stripe rust resistance genes have been explored in D. villosum [ 52 ].…”
Section: Discussionmentioning
confidence: 99%